Deficiencies causes in road construction scheduling: Perspectives from construction professionals - Karen Castañeda; Omar Sánchez; Rodrigo F. Herrera; Guillermo Mejía (Heliyon)
Effective construction scheduling is crucial for the success of road projects. However, deficiencies in this scheduling can lead to significant challenges such as delays, cost overruns, and litigation. Therefore, project managers need to understand the causes that contribute to these deficiencies thoroughly. Unfortunately, there has been little research examining these elements in detail. To address this gap, this study examined the causes that affect the scheduling of construction processes for road projects. The research method involved four stages: (1) identification of causes affecting construction scheduling, (2) design and application of a questionnaire, (3) influence analysis, and (4) exploratory quantitative analysis. The study identified 34 causes of deficiencies in the scheduling of road construction processes in six categories: workforce, machinery, material, measurement, environment, and method. Thirty-two experts were consulted to evaluate the frequency and severity of each cause based on a relative influence index. The causes with the greatest impact on deficiencies in road construction scheduling were poor estimation of labor performance, poor estimation of workforce quantity, and deficient coordination with public utilities. The findings allow managers to pinpoint the root causes of road construction planning problems and identify effective solutions.